Serial millisecond crystallography for routine room-temperature structure determination at synchrotrons - Tobias Weinert (Nature Portfolio, 2017)
Serial crystallography was developed for protein crystal data collection with X-ray free-electron lasers. Here the authors present several examples which show that serial crystallography using high-viscosity injectors can also be routinely employed for room-temperature data collection at synchrotrons.